2003
DOI: 10.1046/j.1365-2834.2003.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and leadership strategies for managers of nurse practitioners

Abstract: For managers to be most effective, they need to address three challenges that are of a managerial, not clinical, nature. By implementing specific leadership strategies, managers of nurse practitioners can facilitate the introduction of the new role and improve its sustainability in health organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 15 publications
4
102
0
1
Order By: Relevance
“…Addressing such questions in advance can reduce the barriers experienced by NPs and PAs. Challenges for managers comprise clarifying the reallocation of tasks, managing shifting working relationships in the team and continuing to manage the team in an evolving situation (Reay et al 2003). …”
Section: Policy Recommendationsmentioning
confidence: 99%
“…Addressing such questions in advance can reduce the barriers experienced by NPs and PAs. Challenges for managers comprise clarifying the reallocation of tasks, managing shifting working relationships in the team and continuing to manage the team in an evolving situation (Reay et al 2003). …”
Section: Policy Recommendationsmentioning
confidence: 99%
“…[2][3][4] Although these patients are not the primary cause of ED overcrowding, there are longer waiting times and possibly a reduced quality of care for these patients. 5,6 To accommodate more patients, nurse practitioners (NPs) in the United States 7 and, more recently in the United Kingdom, Australia 8,9 and Canada have begun to manage patients who present to EDs with non-urgent and primary health care needs. 10 Introducing NPs into an ED affects the physicians, nursing staff and other health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…They are on their own as they develop protocols and negotiate care provision issues with physicians. This study is consistent with prior research that identified adding the NP role into an existing physician practice takes time and trust as well as the support from management in delineating the roles of the new health care team (Reay, Golden-Biddle, & Germann, 2003;Reay et al, 2006). This study also highlights that when physicians and NPs do not report to the same administration, challenges can arise for the NP in negotiating directly with the physicians on practice issues and development of policy.…”
Section: Support From Managementsupporting
confidence: 90%